Financial services management : a qualitative approach - Falconer, Steward (Routledge, 2014)
"The financial services sector has undergone a period of unprecedented turbulence in recent years, though remains hugely significant to the wider global economy and is an important destination for many thousands of students coming through business and accounting school. Understanding how management concepts apply to this important sector can give graduates a real edge in the jobs market.This new textbook introduces management; focusing on concepts, theories and skills particularly suited to the financial services sector. Beginning with a useful overview of the development of management theories through history, the text then focuses on topical issues such as organizational design, the use of information technology, the development of a marketing orientation, social responsibility, ethics and, the influence of the external business and social environments and organizational development and the management of change.This practical textbook mixes theory with application throughout - employing a variety of case studies and examples to render the topic both accessible and memorable. The result is a resource that will help lecturers teaching management skills and students keen to develop their financial services understanding"